FINDING THE STRATEGY OF SUSTAINABLE COMPETITIVE ADVANTAGE: CORE COMPETENCE ON MELON CULTIVATION WITH RESOURCE-BASED VIEW APPROACH - Suhartini, Suhartini; Muhaimin, Abdul Wahib; Maulidah, Silvana (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Sustainable competitive advantage is an advantage that is achieved continuously by implementing strategies to attain unique values that competitors do not own. This research aims to identify resources and capabilities, analyze core competencies, and formulate strategies for sustainable competitive advantage in melon farming with the Resource-Based View (RBV) approach at Djoyo Tani. The research was conducted in November-December 2023 with a case study type. Respondents were selected by purposive sampling with 7 key informants. The analytical tools used were value chain analysis, VRIO framework analysis, and ANP. The results showed that melon farming has 40 resources and 25 capabilities. The core competencies of melon farming come from 11 resources and 4 capabilities. The most dominant competencies for achieving sustainable competitive advantage are Innovation (0.16163), Melon Cultivation Ability (0.14155), and Green House (0.13187). Meanwhile, alternative business strategies to achieve sustainable competitive advantage that can be implemented by melon farms are differentiation strategies. By implementing a differentiation strategy, Djoyo Tani can bring out its uniqueness or characteristics, so that it can be an attraction for consumers that is not owned by other melon farmers. The differentiation strategies that can be applied by Djoyo Tani in the future are (1) Developing its business horizontally; (2) Developing innovations in the melon cultivation process by applying the concept of smart farming based on the Internet of Things (IoT); and (3) Marketing through the utilization of Digital marketing technology.